2020
DOI: 10.21037/atm-20-7024
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signaling pathway-mediated microRNA-181b promoted blood-brain barrier impairment by targeting sphingosine-1-phosphate receptor 1 in septic rats

Abstract: Background: Blood-brain barrier (BBB) impairment plays a significant role in the pathogenesis of sepsisassociated encephalopathy (SAE). However, the molecular mechanisms are poorly understood. In the present study, we aimed to investigate the regulatory relationship between the Janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathway, microRNA (miR)-181b and its target genes in sepsis in vivo and in vitro.Methods: Four rat models (sham, sepsis, sepsis plus STAT3 inhibitor (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Results of GO and KEGG pathway analyses revealed the signaling pathways in which JAK2 or FOXM1 are involved, which was consistent with the role that JAK2 or FOXM1 played in the development of cancer, such as proliferation [JAK-STAT (32)(33)(34) and ErbB/PI3K-AKT signaling pathway (35), PI3K-AKT/FoxO (36)], anti-apoptosis (p53 signaling pathway), angiogenesis (VEGF signaling pathway), and immune response [JAK-STAT (37)]. The JAK2 component is an important part of JAK-STAT signaling pathway.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Results of GO and KEGG pathway analyses revealed the signaling pathways in which JAK2 or FOXM1 are involved, which was consistent with the role that JAK2 or FOXM1 played in the development of cancer, such as proliferation [JAK-STAT (32)(33)(34) and ErbB/PI3K-AKT signaling pathway (35), PI3K-AKT/FoxO (36)], anti-apoptosis (p53 signaling pathway), angiogenesis (VEGF signaling pathway), and immune response [JAK-STAT (37)]. The JAK2 component is an important part of JAK-STAT signaling pathway.…”
Section: Discussionsupporting
confidence: 67%
“…Survival analysis was conducted to validate the potential clinical benefits of assessing the risk score to guide ICI strategies, which demonstrated that patients with high risk scores were associated with worse OS and PFS (P=0.0018 and P=0.015, respectively). Some previous studies explained that JAK2 and FOXM1 were involved in promoting the pathogenesis of malignancy (32)(33)(34)(35)(36)(37)(38)(39). In addition, the predictive performance of the risk score model on ICBresponse indicated that it may be a potential immunerelated biomarker for LUSC.…”
Section: Discussionmentioning
confidence: 92%
“…The JAK/STAT signaling pathway had been proved to mediate the myocardial injury of septic rats with distinctly higher relative mRNA expression levels of JAK and STAT3 ( Jin et al, 2020 ). Furthermore, JAK2/STAT3 signaling pathway had been demonstrated to induce the expression of miR-181b, which could downregulate sphingosine-1-phosphate receptor 1 (S1PR1) and decrease BBB cell adhesion, thereby promoting BBB impairment in rats with sepsis ( Chen et al, 2020 ). TLR signaling was reported to be involved in cardiac redox signaling, calcium handling, energy metabolism, and affecting cardiac structure and gap junction proteins in sepsis mice ( Lackner et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, IL-1Ra, IL-4, IL-6, IL-10, IL-11, IL-13, IL-35, and TGF-β are some anti-inflammatory cytokines ( Chaudhry et al, 2013 ). Furthermore, some signaling pathways have been reported to relate with sepsis closely, such as the JAK/STAT signaling pathway could mediate the myocardial injury of septic rats ( Jin et al, 2020 ); the PI3K-Akt signaling pathway could attenuate apoptosis and improve the survival in animal models of sepsis ( Liu et al, 2019 ; Mizuta et al, 2020 ); the T-cell receptor signaling pathway could release some activated T cells and nuclear factors, CD4 + , CD8 + , and nuclear factor of activated T cells 2 (NFATC2), to take the immune response against sepsis ( Beckmann et al, 2020 ; Kim et al, 2021 ); the JAK2/STAT3 signaling pathway could promote blood–brain barrier (BBB) impairment in rats with sepsis ( Chen et al, 2020 ); the TLR signaling pathway could play a crucial role in sepsis-induced acute cardiac injury and acute injury of the lungs, kidneys, and intestine ( Krivan et al, 2019 ; Kumar, 2020a ; Lackner et al, 2020 ); the NF-κB/TNF-α signaling pathway could regulate inflammatory apoptosis ( Chand et al, 2018 ) and alleviate the injury of lungs and intestinal barrier in sepsis ( Wang et al, 2020 ; Cao et al, 2021 ). NF-κB could activate the cytokine storm by promoting the transcription of some pro-inflammatory cytokines, including IL-1β, IL-12, and TNF-α ( Hotchkiss et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, microRNA-218 hampers the release of inflammatory factors in the serum by suppressing the JAK/STAT pathway and reversely modulating VOPP1, thereby delaying the progression of sepsis in mice [ 20 ]. Also, the JAK2/STAT3 pathway-induced miR-181b intensifies blood-brain barrier damage in septic rats by targeting the down-regulation of sphingosine-1-phosphate receptor 1 (S1PR1) [ 21 ]. Recent studies have revealed that targeting those inflammatory pathways makes much sense in treating sepsis.…”
Section: Introductionmentioning
confidence: 99%